2009
DOI: 10.1504/ijsss.2009.026508
|View full text |Cite
|
Sign up to set email alerts
|

Financial capital democratisation: recipes for growth and disaster

Abstract: The broadening of access to financial capital otherwise known as financial capital democratisation (FCD), has been receiving increasingly more attention, especially from those who are concerned about poverty, community development and development of entire nations. This concept has also its roots in ethical and religious based economic systems. In this paper we review various FCD systems. Our main conclusions are that the current crisis is due to severe adverse selection and moral hazard problems, that a new t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In response to this, recent researchers have suggested that excessive financial growth may lead to macroeconomic instability, particularly the strength of inflationary pressures (Calza et al, 2006;Bayoumi and Melander, 2008;Ramady and Kantarelis, 2009). As more FIN of private credit and liquid liabilities (LL) circulates in the economy, more goods can be purchased and aggregate demand increases which pushes prices upwards (Lipsey, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to this, recent researchers have suggested that excessive financial growth may lead to macroeconomic instability, particularly the strength of inflationary pressures (Calza et al, 2006;Bayoumi and Melander, 2008;Ramady and Kantarelis, 2009). As more FIN of private credit and liquid liabilities (LL) circulates in the economy, more goods can be purchased and aggregate demand increases which pushes prices upwards (Lipsey, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As more FIN of private credit and liquid liabilities (LL) circulates in the economy, more goods can be purchased and aggregate demand increases which pushes prices upwards (Lipsey, 1999). Arguably, Ramady and Kantarelis (2009) suggested that the rapid expansion of FIN, particularly consumer credit, is fuelling inflation as domestic banks, flooded with governmentdriven money, supply expansion and expanded loan books. Likewise, Bayoumi and Melander (2008) highlighted that excess liquidity reduces the effectiveness of monetary policy transmission, especially affecting the demand side, to reach the targeted inflation.…”
Section: Introductionmentioning
confidence: 99%
“…This short-term approach of the poor can be attributed to their lack of assets (Sherraden, 1991). Furthermore, the poor have limited access to financial services (Ramady and Kantarelis, 2009).…”
Section: Business Strategy and Sustainable Development At The Bopmentioning
confidence: 99%
“…The reasons they espoused include: a) over-reliance on information systems (IS) use in their operations; b) potential for large losses emanating from breaches in their operations; and c) the need to maintain a good public image and assure the confidentiality and integrity of their data and IS assets. In addition, GFSI are sub-jected to strict regulatory oversight (Ramady & Kantarelis, 2009;Delimatsis, 2013;Fernandes, 2013). Indeed, the DTTL (2012, p.2) concluded that " [w]ith increasing business demands and evolving regulatory frameworks, information security is a top priority for financial services industry organizations.…”
Section: Introductionmentioning
confidence: 99%